Improving Cotton Fabric Dyeability by Oxygen Plasma Surface Activation - Víctor M. Serrano-Martínez; Carlos Ruzafa-Silvestre; Carlota Hernández-Fernández; Elena Bañón-Gil; Francisca Arán-Ais; Elena Orgilés-Calpena (Surfaces)
This paper focuses on investigating the use of low-pressure oxygen plasma as a surface treatment aimed at enhancing the wettability and dyeability of cotton fabrics for use in textiles and footwear materials. Plasma activation modified the cotton fabric surfaces, increasing their affinity for polar liquids. The research thoroughly characterised the treated fabrics through a combination of analytical methods and physical testing. Plasma treatment was performed using a 13.56 MHz RF generator at 90 W power, with an oxygen flow rate of 500 sccm and a pressure of 0.30 mbar, for treatment durations of 30, 60, and 120 s. Changes in surface chemistry were analysed with XPS, while SEM was used to observe morphological changes. Static water contact angle measurements confirmed a reduction from 128.5° in untreated cotton to 25.6° in samples treated for 30 s, indicating a significant increase in hydrophilicity. Water absorption tests showed a maximum absorption capacity of 119.6% after 60 min for plasma-treated samples, compared to 65.7% for untreated cotton. Contact angle measurements verified that surface hydrophilicity increased following the treatment. Furthermore, physical tests, such as rub fastness, colourimetry, and water absorption, were carried out to evaluate improvements in wettability, dyeability, and overall performance. The results showed notable enhancements in the wetting properties of cotton textiles, enabling better absorption of water and dyes, along with improved fixation. The comprehensive characterisations provided insights into the mechanisms behind these improvements. This research offers a sustainable approach for the textile industry, as plasma technology is a dry process that enhances dyeing efficiency while maintaining fabric performance and lowering environmental impact.